Variation in the diazotrophic community in a vertical soil profile contaminated with antimony and arsenic. (15th December 2021) - Li, Yongbin; Lin, Hanzhi; Gao, Pin; Yang, Nie; Xu, Rui; Sun, Xiaoxu; Li, Baoqin; Xu, Fuqing; Wang, Xiaoyu; Song, Benru; Sun, Weimin
Abstract: A nitrogen (N) deficiency will usually hinder bioremediation efforts in mining-derived habitats such as occurring in mining regions. Diazotrophs can provide N to support the growth of plants and microorganisms in these environments. However, diazotrophic communities in mining areas have been not studied frequently and are more poorly understood than those in other environments, such as in agricultural soils or in the presence of legumes. The current study compares the differences in depth-resolved diazotrophic community compositions and interactions in two contrasting sites (to depths of 2 m), including a highly contaminated and a moderately contaminated site. Antimony (Sb) and arsenic (As) co-contamination induced a loosely connected biotic interaction, and a selection of deep soils by diazotrophic communities. Multiple lines of evidence, including the enrichment of diazotrophic taxa in the highly contaminated sites, microbe–microbe interactions, environment–microbe interactions, and a machine learning approach (random forests regression), demonstrated that Rhizobium was the keystone taxon within the vertical profile of contaminated soil and was resistant to the Sb and As contaminant fractions. All of these observations suggest that one diazotroph, Rhizobium, may play an important role in N fixation in the examined contaminated sites. Graphical abstract: Image 1 Highlights: Co-contamination reduced nifH abundance of diazotrophic community. Co-contamination induced a loosely connected biotic interaction. Rhizobium was identified as the keystone taxon in Sb and As co-contaminated soil. The taxon of Rhizobium was resistant to the Sb and As based on RF analyses. Abstract : A Sb- and As-induced decline in an alpha diversity was observed with a loosely connected biotic interaction and soil depth selection for diazotrophic communities. Rhizobium was identified as the keystone diazotroph.